2021
DOI: 10.1039/d1dt02611a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aliphatic acyl and aromatic thioamide substituents on the anticancer activity of Ru(ii)-p-cymene complexes with acylthiourea ligands—in vitro and in vivo studies

Abstract: Six different acylthiourea ligands (L1-L6) and their corresponding Ru(II)-p-cymene complexes (P1-P6) were designed to explore the structure-activity relationship of the complexes under the influence of aliphatic chain length and aromatic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…This bond distance was shorter in the case of Ru(II)−benzene (2.590−2.622 Å) complexes containing bidentate acylthiourea ligands over their Ru(II)−p-cymene (2.642−2.839 Å) counterparts with monodentate acylthiourea ligands as well as the uncoordinated ligands (2.660−2.681 Å). 14 The H-bond length had negligible changes in B1 (2.621 Å) and B2 (2.622 Å), however became shorter in the case of B4 (2.590 Å), indicating that the alkyl chain length difference at the Cterminal had a greater influence over the aromatic conjugation at the N-terminal. The structural alterations between the Ru− p-cymene complexes (P2 and P4) (monodentate) and the Ru−benzene (B2 and B4) (bidentate) complexes were quite significant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This bond distance was shorter in the case of Ru(II)−benzene (2.590−2.622 Å) complexes containing bidentate acylthiourea ligands over their Ru(II)−p-cymene (2.642−2.839 Å) counterparts with monodentate acylthiourea ligands as well as the uncoordinated ligands (2.660−2.681 Å). 14 The H-bond length had negligible changes in B1 (2.621 Å) and B2 (2.622 Å), however became shorter in the case of B4 (2.590 Å), indicating that the alkyl chain length difference at the Cterminal had a greater influence over the aromatic conjugation at the N-terminal. The structural alterations between the Ru− p-cymene complexes (P2 and P4) (monodentate) and the Ru−benzene (B2 and B4) (bidentate) complexes were quite significant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The structural alterations between the Ru− p-cymene complexes (P2 and P4) (monodentate) and the Ru−benzene (B2 and B4) (bidentate) complexes were quite significant. 14 CS bond angle was higher in the case of P2 (120.18°) and P4 (120.86°) over B2 (108.93°) and B4 (109.33°). 14 These changes indicated that the ligand underwent configurational changes to accommodate a four-membered ring system within the complex structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Paltan Laha with co-authors came to the same conclusion while investigating several mononuclear cyclometalatediridium(III) complexes towards the human breast cancer cell line (MCF-7) [45]. On the other hand, Swaminathan and her team came to a different conclusion after studying six novel Ru(II)-p-cymene complexes with various acylthiourea ligands against A549 and A549cisR cancer cell lines, as in this case-longer hydrocarbon chain improves the cytotoxicity [46]. Furthermore, in the literature, the copper(II) complexes with phen and alkyl chains with different lengths as ligands show the same pattern [47].…”
Section: Introductionmentioning
confidence: 87%
“…On the other hand, EB penetrates the cells that had lost their membrane integrity, such as late apoptotic and dead cells, giving rise to orange fluorescence. [45,46] AO staining marked the early-stage apoptotic cells as yellow green granular nuclei. Late-stage apoptotic cells were characterized by orange fluorescence of EB staining (Figure 13).…”
Section: Probing the Mode Of Cell Death Through Staining Methodsmentioning
confidence: 99%